The factors that effect on employee performance at Majlis Amanah Rakyat (MARA) Melaka / Ain Nur Afifa Baharudin - Baharudin, Ain Nur Afifa (Faculty of Business and Management, 2019)
Employees are mainly important asset of the organization as they are contributing for the organization’s success. Employee performance will determine achievement and failure of the organizations. Performance is one of the platforms to know whether employees work well or not. However, employee performance based on productivity reported low in Malaysia. The purpose of this research is to investigate Employee performance as dependent variable while financial compensation, recognition, training and development, and retirement benefit as independent variables. The purpose of this research is to investigate the most significant effect of compensation on employee performance at Majlis Amanah Rakyat (MARA) Melaka. This research is a quantitative research which had used the self-administered questionnaire as the instrument for the collection of data. The data was collected and viable at a percentage of 100% out of the possible 150 respondents which was derived from the total population of 150 respondents. Sample selection was based on stratified sampling techniques method. The data collected was then evaluated by using Statistical Package for the Social Science (SPSS) Version 23 Software. Using SPSS, numerous tests were converged such as reliability analysis, frequency distribution, descriptive analysis, Pearson’s correlation analysis and multiple regressions analysis. The results indicated that types of compensation which include financial compensation and recognition, has a positive relationship and significant to employee performance while training and development, and retirement benefit are not significant to employee performance.